(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This paper explores the complexities of translating emotions and feelings into Uzbek and Russian, emphasizing the cultural and linguistic nuances involved. Emotions are not only universal experiences but also deeply influenced by cultural contexts, which affect how they are expressed and understood. The paper discusses key emotional terms in both Uzbek and Russian, highlighting similarities and differences in emotional expression and cultural perspectives. By examining these translations, the paper aims to enhance cross-cultural communication and empathy, providing insights into the rich emotional landscapes of Uzbek and Russian-speaking communities